Interference of Drugs on Clinical Chemistry- Shall We Start Thinking? - Yadav, Sharda; KC, Sanjaya (Journal of Nepal Chemical Society, 2013)
Clinical chemistry is emerging area in the field of clinical medicine which deals with the estimation of different analytes from body fluids. Different drugs interfere with the estimation of these analyte. The interference can be either physiological or analytical. Out of many analytes the most commonly estimated analyte are glucose, urea, creatinine, sodium and potassium. Small changes in these analytes also might give misleading information to the clinician. Though the clinicians will be aware of the major side effects of the drug, minor physiological effect might be overlooked also the analytical procedure and the effect of drug in different analytes. Hence, it is necessary for laboratory to inform clinicians regarding the possible effects of drugs on analytes. DOI: http://dx.doi.org/10.3126/jncs.v29i0.9257 Journal of Nepal Chemical Society Vol. 29, 2012 Page: 89-95 Uploaded date: 12/5/2013